Social justice versus justice in social encyclicals - GAŁKOWSKI, TOMASZ (Prawo Kanoniczne, 2018)
The author of the study poses a question concerning the ontic status of social justice and its reference to fundamental formula of justice. He presents the prevailing views and carries out analysis referring to the Popes’ social encyclicals. Social justice is depicted as a metaphor of justice. Their common content is what is described as a due thing (therefore justice). The difference between them lies in what concerns the cause of the object of justice and the way of defining its standard. Moreover, social justice lacks mutual acknowledgement of engaged parties.